2006
DOI: 10.1007/s10350-005-0225-3
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Perforations After Barium Enema: A Review

Abstract: Rectal perforations after barium enema are rare. The overall mortality rate decreased in recent decades from approximately 50 to 35 percent as the result of advances in supportive and intensive care. Because of these advances, more aggressive surgical strategies were undertaken. With the advent of endoscopy, less barium enemas are performed. Consequently, the absolute incidence of complications has decreased. It is expected that in the future barium enemas will be replaced by more sensitive and less risky tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
1
11

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 115 publications
(145 reference statements)
0
56
1
11
Order By: Relevance
“…[35][36][37] Barium enema pressures of around 40 mmHg are necessary to perform an adequate double contrast study. 20,22,38 Human studies have shown that the luminal pressure needed to perforate the colon is higher than that: lowest in the cecum, and highest in the rectum.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37] Barium enema pressures of around 40 mmHg are necessary to perform an adequate double contrast study. 20,22,38 Human studies have shown that the luminal pressure needed to perforate the colon is higher than that: lowest in the cecum, and highest in the rectum.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, intraluminal lesions such as cancer, diverticulum or rectal biopsies were reported pre-existing factors. 1 Rectal perforations may be either intraperitoneal or extraperitoneal. Five types of perforations have been described based upon anatomic boundaries.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis is based on the clinical and imaging studies. 1 The radiographic findings depend upon the volume of extravased air and barium.…”
Section: Introductionmentioning
confidence: 99%
“…Several different treatment approaches have been employed for the management of rectal perforations. In a recent review, de Feiter et al [12] noted that surgery is not always indicated for rectal perforation occurring after a barium enema. Intramural or a small retroperitoneal perforation can be treated with conservative measures such as bowel rest, total parenteral feeding, intravenous fluids and broad-spectrum antibiotics.…”
Section: Discussionmentioning
confidence: 99%